Utilization of E-Resources for Learning Among Undergraduates - Florence Olutunu Daramola (Indonesian Journal of Educational Research and Technology, 2023)
This study determined the utilization of e-resources for learning among undergraduates. The study adopted descriptive research of the survey type. The population for this study consists of all National Open University of Nigeria (NOUN) undergraduates. Proportional sampling techniques were used to allocate many respondents in each NOUN centre based on their estimated population using Israel Model. The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of statistical product and service solution (SPSS) version 20.0 at a 0.05 level of significance. The findings indicated that undergraduate students had positive utilization of E-resources for learning. No significant difference exists in the undergraduate students’ utilization of E-resources for learning based on gender and digital age. The study concluded that learning can be enhanced among undergraduate students if appropriate resources are deployed for learning. Therefore, it was recommended that undergraduate students be encouraged to deploy e-resources for learning irrespective of their gender.